Positive relationship between crop centrality and pollination service - Allasino, Mariana Laura; Haedo, Joana P.; Lázaro, Amparo; Torretta, Juan Pablo; Marrero, Hugo Javier (Elsevier, 2022)
The topological structure of interaction networks determines community dynamics and stability. Closeness centrality is a species-level attribute that measures the relative position and proximity of species in the interaction network. We assessed the link between closeness centrality of crops in plant-pollinator interaction networks and crop seed production. We worked with five crop species used for seed production distributed in 14 farms. At each farm we recorded pollinators’ interactions with the crop and with the co-flowering plants at crop edges and built quantitative plant-pollinator interaction networks. For each network, we calculated weighted closeness centrality of crops and related it to crop seed set by using generalized linear mixed models. Our results show that crop centrality is positively associated with crop seed production, and suggest that the use of ecological interaction network metrics in agricultural systems could be useful to design agronomic management plans and enhance crop yields.